Lightweight Concrete Reinforced with Polypropylene Fibers - Ali Jihad Hamad (Institute of Advanced Engineering and Science, 2015)
This research study the mechanical properties of lightweight concrete reinforced with polypropylene fibers. Foam agent used to produce lightweight foamed concrete. The aim of this study to investigate the effect of polypropylene fibers on mechanical properties of lightweight foamed concrete. The volume fractions of the polypropylene fibers (PPF) used are: 0.0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% total volume of concrete. The flowability, dry density, compressive strength and splitting tensile strength, were measured. The results shows, the flowability of lightweight foamed concrete reduced by addition polypropylene fibers. The compressive strength and splitting tensile strength increased with rising the percentages of polypropylene fibers.This research study the mechanical properties of lightweight concrete reinforced with polypropylene fibers. Foam agent used to produce lightweight foamed concrete. The aim of this study to investigate the effect of polypropylene fibers on mechanical properties of lightweight foamed concrete. The volume fractions of the polypropylene fibers (PPF) used are: 0.0%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5% total volume of concrete. The flowability, dry density, compressive strength and splitting tensile strength, were measured. The results shows, the flowability of lightweight foamed concrete reduced by addition polypropylene fibers. The compressive strength and splitting tensile strength increased with rising the percentages of polypropylene fibers.